"The growing house" in Alvar Aalto’s AA-System - Fernández-Vivancos González, Enrique (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2018)
In 1940, once the Second World War had started, Alvar Aalto and the M.I.T agreed on the creation of a research laboratory for the problem of re-construction, aimed at developing systems for housing prefabrication for the relocation of displaced population. In this laboratory, Aalto focused on the study of “the growing house”, in reference to a case from the ancient Finnish culture which he was interested in advocating in that particular and delicate political moment: the popular architecture of Karelia. Despite its brevity, this research linking technical culture and vernacular tradition inspired a clear majority of the studies on prefabrication carried out in Finland in the 1940s, and can be translated into the proposal of the AA-system, which Aalto developed for the company A. Ahlsmtröm. This article analyzes how this experience was developed, framing it within a post-conflict reconstruction period in which North American technology was transferred to the Finnish context and met the aspiration for recovering the human dimension which was lost in the industrialization processes. This reflection was promoted by Aalto through initiatives such as the Research Laboratory for Reconstruction, the AA-system or the Standardization Bureau, and finally resulted in the formulation of the concept of “flexible standardization”.